2013
DOI: 10.1136/archdischild-2013-304428
|View full text |Cite
|
Sign up to set email alerts
|

Does prompt treatment of urinary tract infection in preschool children prevent renal scarring: mixed retrospective and prospective audits

Abstract: ObjectiveTo test whether active management of urinary tract infections (UTI) in young children by general practitioners can reduce kidney scarring rates.DesignA comparison of two audits in Newcastle, of children aged <8 years, presenting with UTIs ; a retrospective audit of conventional management during 1992–1995 (1990s) versus a prospective audit of direct access management during 2004–2011 (2000s).Main outcome measuresKidney scarring rates, and their relationship with time-to-treat.ResultsChildren with a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 26 publications
(26 reference statements)
2
38
0
4
Order By: Relevance
“…A delay in treatment has been associated with a higher likelihood of renal scarring. [8][9][10][11] This may partly explain why, in a recent meta-analysis, children with UTIs caused by non-E coli organisms were more likely to develop renal scarring. 12 Our results suggest that pyuria may not always be present in children with UTIs, especially those caused by Enterococcus species, Klebsiella species, or P aeruginosa.…”
Section: Figurementioning
confidence: 99%
“…A delay in treatment has been associated with a higher likelihood of renal scarring. [8][9][10][11] This may partly explain why, in a recent meta-analysis, children with UTIs caused by non-E coli organisms were more likely to develop renal scarring. 12 Our results suggest that pyuria may not always be present in children with UTIs, especially those caused by Enterococcus species, Klebsiella species, or P aeruginosa.…”
Section: Figurementioning
confidence: 99%
“…4 A recent study emphasised the importance of prompt and empirical antibiotic treatment of childhood UTI. 5 When the threshold for prescribing antibiotics for children with non-specific symptoms is low, children with 'occult UTI' may be serendipitously treated for their UTI. 6 A small UK study found that children with UTI that had not been suspected by the GP had all received antibiotics (amoxicillin) for alternative infections.…”
Section: Introductionmentioning
confidence: 99%
“…Timely diagnosis and antibiotic therapy are necessary to reduce the risk of serious complications from UTI (2). However, due to nonspecific manifestations, UTI requires a high degree of suspicion, which in turn has contributed to both underand overdiagnosis (3,4).…”
mentioning
confidence: 99%